Symbol

# Calculator search results

Formula
Solve the equation
Graph
$y = \dfrac { 1 } { 2 } x + \dfrac { 1 } { 3 }$
$y = - \dfrac { 1 } { 6 }$
$x$Intercept
$\left ( - \dfrac { 2 } { 3 } , 0 \right )$
$y$Intercept
$\left ( 0 , \dfrac { 1 } { 3 } \right )$
$\dfrac{ 1 }{ 2 } x+ \dfrac{ 1 }{ 3 } = - \dfrac{ 1 }{ 6 }$
$x = - 1$
 Solve a solution to $x$
$\color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ x } + \dfrac { 1 } { 3 } = - \dfrac { 1 } { 6 }$
 Calculate the multiplication expression 
$\color{#FF6800}{ \dfrac { x } { 2 } } + \dfrac { 1 } { 3 } = - \dfrac { 1 } { 6 }$
$\color{#FF6800}{ \dfrac { x } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 3 } } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 6 } }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 2 } { 3 } } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
$x \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 2 } { 3 } } = - \dfrac { 1 } { 3 }$
 Move the constant to the right side and change the sign 
$x = - \dfrac { 1 } { 3 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 2 } { 3 } }$
$x = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 3 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 2 } { 3 } }$
 Find the sum or difference of the fractions 
$x = \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture